Early stage and long term treatment of multiple sclerosis with interferon-β - Angela Applebee (Dove Medical Press, 2009)
Angela Applebee, Hillel PanitchDepartment of Neurology, University of Vermont College of Medicine, and Neurology Service, Fletcher Allen Health Care, Burlington, VT, USAAbstract: Multiple sclerosis (MS) affects young adults during the most productive years of their lives, and until recently many neurologists were limited to treating symptoms and attacks without any ability to alter the disease course. The 1990s ushered in an era of possibility with the approval of three interferon-beta (IFNβ) therapies for the treatment of MS. Though the mechanism of action of these agents is not completely understood, it is clear they reduce magnetic resonance imaging (MRI) activity as well as improve clinical outcomes. The principal randomized, blinded, multicenter trials of IFNβ all point to the need for early treatment soon after the diagnosis of MS is made. Efficacy has also been shown in patients treated after a first demyelinating event. Data on IFNβ in the treatment of secondary progressive MS (SPMS) is not impressive, although it shows some benefit in SPMS patients who continue to experience MRI activity and clinical relapses, signifying a continued inflammatory component to their disease. There has been no proven efficacy of IFNβ in the treatment of primary progressive MS (PPMS). The IFNβ therapies are generally well tolerated with a favorable side effect profile. Despite benefits in MRI and clinical measures such as relapse rates and Expanded Disability Status Scale progression, patients continue to exhibit clinical progression and radiological atrophy, pointing to confounding factors and perhaps multiple etiologies of a disease that is not yet fully understood. In addition, the subject of neutralizing antibodies has recently assumed importance. The significance of these on treatment efficacy is uncertain, and until a universally accepted reliable assay is adopted, the decision to change treatment continues to rely on the clinical interpretation of the patient’s history and physical examination. Additional recommendations for management of patients, informed by the best available evidence, are also presented. Keywords: interferon-β, multiple sclerosis, clinical trials, neutralizing antibodies